Viral Diseases of Strawberries - Catalina Moyer; Vance M. Whitaker; Natalia A. Peres (EDIS)
PP273, a 7-page illustrated fact sheet by Catalina Moyer, Vance M. Whitaker, and Natalia A. Peres, provides basic information on viral diseases of strawberries with particular emphasis on the presence of strawberry necrotic shock virus (SNSV) on Florida strawberry plants. Includes references. Published by the UF Department of Plant Pathology, April 2010.